Hospital Performance in Brazil : The Search For Excellence - La Forgia, Gerard M. (World Bank, Washington, DC, 2012)
Hospitals are at the center of the health care universe in Brazil. When ill, many Brazilians go straight to the hospital for want of a family doctor or primary care network. Hospitals are a critical part of the government's budget, absorbing nearly 70 percent of public spending on health. Hospitals influence the ebb and flow of politician's careers when hospital mishaps hit the headlines or the limelight falls on high-performing hospitals. Hospitals are at the forefront of policy discussions in Brazil. The discussions reflect their promise as centers of technological innovation and medical advances as well as widespread concern about their cost and quality. Brazilian hospitals are important to many people for many different reasons. What makes hospitals important is easy to understand. What makes hospitals deliver quality care efficiently or not is much harder to grasp. Can Brazil improve the performance of its hospitals? The evidence presented in this volume suggests that the answer is yes. However, it will take strong leadership, coordinated efforts of federal, state, and municipal governments, direct engagement with the private health sector, and systematic but continuous vision, policies, and actions. Such enabling factors have been generally weak or absent in the Brazilian health system. Promising initiatives have often been gutted or scrapped after changes of government.